Analysing the relationship between tourism development and sustainability by looking at the impact on the environment: A study on the European Union countries - Cristiana Păvăluc (Melinte); Alexandru Anichiti; Valentin Niţă; Gina Ionela Butnaru (CES Working Papers, 2020)
The relationship between environment and tourism is complex and based on interdependence. Tourism can have both a negative and a positive environmental impact. The aim of this paper is to analyse the relationship between tourism development and environmental sustainability. The results show that tourism development is one of the causes of the deterioration of the environmental resources on which we depend. As tourism becomes more important and a higher number of people are travelling over borders, tourism has a growing environmental impact. However, tourism also has the potential to create beneficial effects on the environment by contributing to environmental protection and conservation.
Keywords: 330; tourism development; sustainability; the environment; impact